The Prognostic Value of Family History for the Estimation of Cardiovascular Mortality Risk in Men: Results from a Long-Term Cohort Study in Lithuania. - Abdonas Tamosiunas; Ricardas Radisauskas; Jurate Klumbiene; Gailute Bernotiene; Janina Petkeviciene; Dalia Luksiene; Dalia Virviciute; Vilija Malinauskiene; Olga Vikhireva; Vilius Grabauskas (PLoS ONE, 2015)
To evaluate the additional prognostic value of family history for the estimation of cardiovascular (CVD) mortality risk in middle-aged urban Lithuanian men.The association between family history of CVD and the risk of CVD mortality was examined in a population-based cohort of 6,098 men enrolled during 1972-1974 and 1976-1980 in Kaunas, Lithuania. After up to 40 years of follow-up, 2,272 deaths from CVD and 1,482 deaths from coronary heart disease (CHD) were identified. Multivariate Cox proportional hazards models were used to estimate hazard ratios (HR) for CVD and CHD mortality.After adjustment for traditional CVD risk factors, the HR for CVD mortality was 1.24 (95% CI 1.09-1.42) and for CHD mortality 1.20 (1.02-1.42) in men with first-degree relatives having a history of myocardial infarction (MI), compared to men without positive family history. A significant effect on the risk of CVD and CHD mortality was also observed for the family history of sudden cardiac death and any CVD. Addition of family history of MI, sudden death, and any CVD to traditional CVD risk factors demonstrated modest improvement in the performance of Cox models for CVD and CHD mortality.Family history of CVD is associated with a risk of CVD and CHD mortality significantly and independently of other risk factors in a middle-aged male population. Addition of family history to traditional CVD risk factors improves the prediction of CVD mortality and could be used for identification of high-risk individuals.